2015
DOI: 10.1098/rsbl.2015.0767
|View full text |Cite
|
Sign up to set email alerts
|

Synchrony and exertion during dance independently raise pain threshold and encourage social bonding

Abstract: Group dancing is a ubiquitous human activity that involves exertive synchronized movement to music. It is hypothesized to play a role in social bonding, potentially via the release of endorphins, which are analgesic and reward-inducing, and have been implicated in primate social bonding. We used a 2 × 2 experimental design to examine effects of exertion and synchrony on bonding. Both demonstrated significant independent positive effects on pain threshold (a proxy for endorphin activation) and in-group bonding.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
301
3
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 300 publications
(322 citation statements)
references
References 25 publications
14
301
3
4
Order By: Relevance
“…Similar results are seen when adults dance together in synchrony. After this experience, they are more cooperative (Reddish et al, 2013), can remember more visual details about one another (Woolhouse, Tidhar & Cross, 2016), experience increased pain thresholds, and have greater feelings of group cohesion (Tarr et al, 2015) compared to those dancing out-of-synchrony.…”
Section: Oving In Time With Others Ormentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results are seen when adults dance together in synchrony. After this experience, they are more cooperative (Reddish et al, 2013), can remember more visual details about one another (Woolhouse, Tidhar & Cross, 2016), experience increased pain thresholds, and have greater feelings of group cohesion (Tarr et al, 2015) compared to those dancing out-of-synchrony.…”
Section: Oving In Time With Others Ormentioning
confidence: 99%
“…When adults walk, row, tap, dance, or sing in synchrony with one another, affiliative behaviors such as trust, cooperation, and ratings of likeability are encouraged (Anshel & Kipper, 1988;Hove & Risen, 2009;Reddish, Fischer, & Bulbulia, 2013;Tarr, Launay, Cohen, & Dunbar, 2015;Valdesolo, Ouyang, & DesSteno, 2010;Weinstein, Launay, Pearce, Dunbar, & Stewart, 2015;Wiltermuth & Heath, 2009). Even 4-year-old children who play together in a musical versus a nonmusical way are later more helpful and cooperative with one another (Kirschner & Tomasello, 2010).…”
Section: Oving In Time With Others Ormentioning
confidence: 99%
“…Kinaesthetic empathic responsiveness to a client's movement repertoire is essential to developing a therapeutic alliance (Samaritter & Payne, 2013). Synchronous, effortful movement together nurtures the embodied relationship (Tarr, Launay, Cohen & Dunbar, 2015) and provides the therapist with a body felt-sense of the client's actions, emotions and sensory experiences facilitated by mirror neurones and embodied simulation (Berrol, 2006;Gallese & Sinigaglia, 2011). Attunement (connecting in rhythm) and adjustment (connecting in shape) can be part of the experience of mirroring (Kestenberg-Amighi; Loman, Lewis, Sossin, 1999).…”
Section: Techniques and Methodsmentioning
confidence: 99%
“…The therapist is bodily engaged in the active, expressive movement dialogue and expression, she is relating non-verbally to participants including their movements (whether they are conscious of this or not) to form a cohesive group process nurturing a sense of belonging. Research has demonstrated that this synchronous group process of dancing together to music can reduce pain and increase social bonding (Stone et al, 2015).…”
Section: Embodied Simulationmentioning
confidence: 99%